1998
DOI: 10.5694/j.1326-5377.1998.tb123426.x
|View full text |Cite
|
Sign up to set email alerts
|

Latent cochlear damage in personal stereo users: a study based on click‐evoked otoacoustic emissions

Abstract: Objective To assess the effects of use of personal stereo systems (PS) on hearing by means of the objective measure of transient‐evoked otoacoustic emissions. Participants and setting People aged between 10 and 59 years who had otoacoustic emissions recorded by the National Acoustic Laboratories between 1989 and 1997 were eligible for inclusion. Recordings from participants with hereditary disorders or any form of aural disease (eg, otitis media, otosclerosis, fluctuant hearing loss, Meniere's syndrome, or exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 9 publications
1
28
0
2
Order By: Relevance
“…Cross-sectional studies have shown that OAEs are sensitive indicators of permanent noise-induced damage to the inner ear in groups of noise-exposed people, with lower OAE levels associated with higher audiometric thresholds ͑e.g., LePage and Murray, 1998;Desai et al, 1999;Mansfied et al, 1999;Attias et al, 2001͒. Furthermore, noise-exposed people tend to have lower OAEs than people with similar audiometric thresholds but no noise exposure ͑Bicciolo et Murray and LePage 1993;Attias et al, 1995Attias et al, , 1998Xu et al, 1998;Desai et al, 1999;Attias et al, 2001͒.…”
Section: Introductionmentioning
confidence: 90%
“…Cross-sectional studies have shown that OAEs are sensitive indicators of permanent noise-induced damage to the inner ear in groups of noise-exposed people, with lower OAE levels associated with higher audiometric thresholds ͑e.g., LePage and Murray, 1998;Desai et al, 1999;Mansfied et al, 1999;Attias et al, 2001͒. Furthermore, noise-exposed people tend to have lower OAEs than people with similar audiometric thresholds but no noise exposure ͑Bicciolo et Murray and LePage 1993;Attias et al, 1995Attias et al, , 1998Xu et al, 1998;Desai et al, 1999;Attias et al, 2001͒.…”
Section: Introductionmentioning
confidence: 90%
“…However, the differences in TEOAE responses may be caused by a smaller ear canal volume in children than in adults (Bray and Kemp, 1987). The influence of aging on TEOAEs has been described as decreasing TEOAE occurrence with increasing age, independent of pure tone hearing threshold levels (Le Page and Murray, 1998). However, Bertoli and Probst (1997) and Prieve and Falter (1995) demonstrated that in adults with good hearing thresholds at low and middle frequencies, no influence of age on OAEs could be observed.…”
Section: Introductionmentioning
confidence: 92%
“…Therefore OAEs are considered to be at least as sensitive to detect small noiseinduced changes in the auditory system as the hearing thresholds. This could be confirmed by several studies ͑Attias et al., 1995;Desai et al, 1999Hotz et al, 1993Kowalska and Sulkowski, 1997;LePage and Murray, 1998;Lucertini et al, 2002;Murray and LePage, 1998;Sliwinska-Kowalska and Kotylo, 2002͒, suggesting that OAE might be used as an early warning sign of noise-induced hearing loss. A direct relation between OAE level and the hearing threshold is not fully established ͑Avan et al ͑1991͒; Bonfils and Avan ͑1992͒; Gaskill and Brown ͑1993͒; Gorga et al ͑1993͒͒.…”
Section: Introductionmentioning
confidence: 94%